2019
DOI: 10.1111/pce.13543
|View full text |Cite
|
Sign up to set email alerts
|

Coordination and trade‐offs between leaf and stem hydraulic traits and stomatal regulation along a spectrum of isohydry to anisohydry

Abstract: The degree of plant iso/anisohydry, a widely used framework for classifying species‐specific hydraulic strategies, integrates multiple components of the whole‐plant hydraulic pathway. However, little is known about how it associates with coordination of functional and structural traits within and across different organs. We examined stem and leaf hydraulic capacitance and conductivity/conductance, stem xylem anatomical features, stomatal regulation of daily minimum leaf and stem water potential (Ψ), and the ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 56 publications
(128 reference statements)
3
46
0
Order By: Relevance
“…This same mechanism is described even within a single fern species (Athyrium filixfemina) that displays different fronds with contrasting C leaf (Cardoso et al, 2019). Interestingly, the relationship between T 50 (the time at which g s is at 50%) and C leaf has also been observed in angiosperm tree species differing in their degree of iso-and anisohydry (Fu et al, 2019), although they presented higher overall T 50 values than those reported for ferns and conifers. Figure 4b shows that stomatal closure, even at the fastest rate reported in Martins et al (2016), does not prevent Ψ leaf decrease when C leaf is low.…”
Section: A 'Buffering' Role Under High Transpirationsupporting
confidence: 62%
See 4 more Smart Citations
“…This same mechanism is described even within a single fern species (Athyrium filixfemina) that displays different fronds with contrasting C leaf (Cardoso et al, 2019). Interestingly, the relationship between T 50 (the time at which g s is at 50%) and C leaf has also been observed in angiosperm tree species differing in their degree of iso-and anisohydry (Fu et al, 2019), although they presented higher overall T 50 values than those reported for ferns and conifers. Figure 4b shows that stomatal closure, even at the fastest rate reported in Martins et al (2016), does not prevent Ψ leaf decrease when C leaf is low.…”
Section: A 'Buffering' Role Under High Transpirationsupporting
confidence: 62%
“…Figure 4b shows that stomatal closure, even at the fastest rate reported in Martins et al (2016), does not prevent Ψ leaf decrease when C leaf is low. Hence, the simulation presented here implies that the stomatal response reported in Martins et al (2016) and Fu et al (2019) possibly reflects a passive hydraulic response to a sudden drop in Ψ leaf -driven by the low buffering capacity of species with low C leaf . The active stomatal control in angiosperms in response to water deficits (Brodribb and McAdam, 2011), together with the socalled 'wrong way response' of transient stomatal opening with increased transpiration (Powles et al, 2006;Buckley et al, 2011), lead to a higher sensitivity of angiosperm leaves to sudden Ψ leaf drops (Zhang et al, 2016).…”
Section: A 'Buffering' Role Under High Transpirationmentioning
confidence: 64%
See 3 more Smart Citations